Vessel sealer and divider instrument temperature during laparoscopic ovariectomy in horses. (3rd December 2017) - Easley, Jeremiah T.; McGilvray, Kirk C.; Hendrickson, Dean A.; Bruemmer, Jason; Hackett, Eileen S.
Abstract: Objective: To determine the temperature of a vessel sealer and divider device during unilateral paralumbar laparoscopic ovariectomy in standing, sedated mares. Study Design: Prospective study. Animals: Fifteen healthy research mares. Methods: Healthy mares with normal ovarian palpation and ultrasonographic appearance were enrolled. Horses were restrained in standing stocks and sedated. A right or left paralumbar ovariectomy was performed with a laparoscopic portal and 2 instrument portals. Ovaries were excised with traumatic forceps and a blunt tip vessel sealer and divider. Temperatures of the vessel sealer and divider were recorded with a thermocouple device adhered to the tip of the instrument. Variables were reported as median and interquartile range (IQR). Results: Surgical time was 30 minutes (IQR, 25‐32) including use of the vessel sealer and the divider for 4.1 minutes (IQR, 3.2‐5.8). The tip of the instrument reached temperatures of 77°C (IQR, 72‐85) during activation and 64°C (IQR, 61‐67) at end cycle. The median increase in end‐cycle instrument tip temperature per activation cycle was 2°C (IQR, −1‐6). All mares returned to their intended use. Conclusion: Despite the instrument temperatures observed during unilateral laparoscopic ovariectomy, surgical complications were minimal. The clinical relevance of the increase in instrument tip temperature of the vessel sealer and divider is presently unclear, but surgeons should use the instrument with caution, especially in close proximity to viscera. The increase in temperature observed at the tip of the vessel sealer and divider during unilateral ovariectomy could be associated with morbidity. The clinical relevance of instrument tip heating during other procedures, such as adhesiolysis and intestinal resection, is unknown and should be evaluated.